DELIRIUM AND RELATED FACTORS IN PATIENTS HOSPITALIZED IN THE INTERNAL INTENSIVE CARE UNIT - Leyla Zengin Aydın; Melik Aksin (International Journal of Health Services Research and Policy)
This study was conducted to examine delirium and its associated factors in patients hospitalized in the internal intensive care unit. The study was conducted in the internal medicine intensive care unit of the University of Health Sciences, Gazi Yaşargil Training and Research Hospital between July 2022 and February 2023. The sample consisted of 103 patients admitted to the internal intensive care unit. Data were collected using the Patient Information Form, Glasgow Coma Scale (GCS), the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU), the Nursing Delirium Screening Scale (Nu-DESC), and the Standardized Mini-Mental Test (SMMT). There were statistically significant differences found in SMMT scores across age groups (F=4.376; p